Pathways, Contributors, and Correlates of Functional Limitation Across Specialties: Workshop Summary. (25th April 2018) - Kritchevsky, Stephen B; Forman, Daniel E; Callahan, Kathryn E; Ely, E Wesley; High, Kevin P; McFarland, Frances; Pérez-Stable, Eliseo J; Schmader, Kenneth E; Studenski, Stephanie A; Williams, John; Zieman, Susan; Guralnik, Jack M
Abstract: Traditional clinical care models focus on the measurement and normalization of individual organ systems and de-emphasize aspects of health related to the integration of physiologic systems. Measures of physical, cognitive and sensory, and psychosocial or emotional function predict important health outcomes like death and disability independently from the severity of a specific disease, cumulative co-morbidity, or disease severity measures. A growing number of clinical scientists in several subspecialties are exploring the utility of functional assessment to predict complication risk, indicate stress resistance, inform disease screening approaches and risk factor interpretation, and evaluate care. Because a substantial number of older adults in the community have some form of functional limitation, integrating functional assessment into clinical medicine could have a large impact. Although interest in functional implications for health and disease management is growing, the science underlying functional capacity, functional limitation, physical frailty, and functional metrics is often siloed among different clinicians and researchers, with fragmented concepts and methods. On August 25–26, 2016, participants at a trans-disciplinary workshop, supported by the National Institute on Aging and the John A. Hartford Foundation, explored what is known about the pathways, contributors, and correlates of physical, cognitive, and sensory functional measures across conditions and disease states; considered social determinants and health disparities; identified knowledge gaps, and suggested priorities for future research. This article summarizes those discussions.